(3GdfXQI GdeSJbHdjI dJcGed GdehGRfI GdYGeI hGdNWW GdbhejI ddJfejIs - (3agej eMehO(B, (3TcQjs ((3YeGf(B:s (3GdefXeI GdYQHjI ddYdhe GdGOGQjI(B,s, 1980)
(3GdJNWjW GdGbJUGOj h GdehGRfI aj GdeYScQ GdGTJQGcj h cPG YdGbJg HGdehGRfI aj GdfXGe GdQCSeGdj h aj GdfXGe GdeNJdW h GdJWQb Gdi eYfi GdehGRfI h NUGFUgG h eSJbHd GdehGRfI GdYGeI h JMbjb GdJfejI aj YbO GdKeGfjfGJ h JfGhd GdeONd Gdi JWhjQ GdehGRfI h fXGe GJdHQGeL cCSdhH dJMbjb GdJcGed eY NWW GdJfejI h OhQ GdfXGe GdeMGSHj GdMchej aj JMbjb GdJcGed(B.s
Keywords: (3GdJfejIs; (3GdejRGfjIs